Binary Gender as a Psychosocial Parameter for Stress, Adaptation, and Coping Among U.S. College Students - Prieto, Denise Nathalie; Ding, Yi; Cho, Su-Je; Ridgard, Tamique; Zhang, Anqi (Advances in Social Sciences Research Journal, 2025)
The present study explored the relationship between binary gender, stress, adaptation, and coping in college students during the COVID-19 pandemic. Study participants were college students ages 18+, attending an institution of higher education in the United States during the global crisis. Because male and female students have been known to experience stress, adaptation, and coping differently, this study randomly selected males (n=91) and females (n=102) and analyzed their responses to validated scale items focusing on the effect of gender, coping, and school adjustment on stress and adaptation to COVID-19 across various domains. Results indicated that gender significantly influenced certain aspects of adaptation, with social and attachment adjustment (6.2% and 5.6% variance explained) being significantly higher among female students, while male students reported greater perceived social support during COVID-19 (5.2% variance explained). Although no significant overall effect of gender on stress and COVID-19 adaptation was found, female students demonstrated a greater reliance on escape-avoidance coping strategies, while male students showed higher perceived social support. Gender differences in discriminatory impact approached significance, suggesting potential disparities in experiences during the pandemic. These findings highlight the need for institutions to implement targeted mental health and academic support interventions to address gender-specific adaptation patterns during crises.